First-in-human dosimetry and safety evaluation of 68Ga-αMSH derivative for PET imaging of melanoma - Samaneh Zolghadri; Mohsen Bakhshi Kashi; Nasim Vahidfar; Saeed Farzanefar; Arezou Karimian; Mohammad Hossein Mohammadi Ashnani; Hassan Yousefnia (Scientific Reports)
Abstract Melanoma remains one of the leading causes of cancer-related mortality worldwide, necessitating advanced imaging techniques for early and accurate detection. This study assesses the dosimetry, safety, and imaging performance of a novel 68Ga-labeled α-melanocyte-stimulating hormone ([68Ga]Ga-αMSH) derivative for targeting melanocortin 1 receptors (MC1Rs) in metastatic melanoma. In this first-in-human, prospective, open-label clinical trial, 11 patients with histologically confirmed metastatic melanoma underwent whole-body PET/CT imaging following intravenous administration of the radiolabeled compound (150 ± 10 MBq). Tumor uptake, biodistribution, pharmacokinetics, and radiation dosimetry were evaluated at 60 and 120 min post-injection. Organ and tumor uptake values were measured as standardized uptake values. Radiation dose estimates were calculated using the MIRD methodology and S-values obtained from OLINDA/EXM software. Safety evaluations included monitoring adverse events, biochemical parameters, and vital signs. The radiopharmaceutical demonstrated rapid and selective uptake in metastatic melanoma lesions, achieving high tumor-to-background contrast within 60 min. Quantitative analysis showed substantial tumor uptake, with sustained activity at 120 min. High tumor-to-blood and tumor-to-muscle ratios ensured excellent lesion detectability. The kidneys exhibited the highest absorbed dose (0.0948 ± 0.0425 mSv/MBq), attributed to renal excretion, whereas the brain received the lowest dose (0.0012 ± 0.0007 mSv/MBq). Comparisons with [18F]FDG and other tracers demonstrated superior dosimetry profiles, minimizing radiation exposure and enabling repeat imaging. Also, safety monitoring revealed no serious adverse events. [68Ga]Ga-αMSH analogue exhibits excellent imaging properties, favorable pharmacokinetics, and a strong safety profile, supporting its clinical utility for PET imaging of metastatic melanoma. Its high tumor specificity and minimal off-target accumulation address limitations associated with [18F]FDG.